The social legitimacy of enterprises recuperated by their workers. An approach based on the notion of moral economy - Rebón, Julián (2016)
The recuperation of enterprises by their workers in Argentina has achieved ample social legitimacy despite its disruptive characteristics. What are the logics that sustain this legitimacy? Does this legitimacy extend to all aspects of the recuperation process, even the most disruptive ones? How do the logics that sustain the legitimacy of the recuperated enterprises interact with the hegemonic values of capitalist society? Through survey research we measured the social value attributed to the recuperation of enterprises and investigated the cultural system in which they emerged and developed. Relying on the concept of moral economy, we affirm that the legitimation of the recuperated enterprises is based on the value that work has in Argentine society as the foundation for social, material, and symbolic reproduction. This cultural valuation of work is the source of understandings of what is just and fair in society and what forms of collective action are legitimate. The cultural valuation of work also sets limits to the commodification of labour.